VISUALISASI STRUKTUR ORGAN ANATOMI HEWAN TERNAK BERBASIS AUGMENTED REALITY - Jimmy Pratama; Bayu Syahputra; Febby Anggellya (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
Over time, the utilization of Augmented Reality (AR) in education is growing, especially in biological science learning media. This study aims to develop a 3D-based Augmented Reality application for visualizing the anatomical organ structure of farm animals, especially cows (Bos taurus) and chickens (Gallus gallus). The application in this study is designed to provide an interactive learning experience with features such as rotation, zoom, and in-depth exploration of the organ structure of farm animals, especially cows and chickens. This research aims to develop Augmented Reality (AR) based learning media that displays the anatomical organ structure of farm animals, such as cows and chickens. The method used as development is Research and Development (R&D) and a qualitative approach to explore user feedback on the application. Development includes needs analysis, design, prototyping, and testing. The results of the qualitative approach, namely interviews, showed that 80% of participants felt that this application was effective in helping to understand animal anatomy. This research concludes that AR is an interesting and effective learning medium, with recommendations for further development using interactive elements and 3D technology.